A Computational Approach to Statistical Learning - Arnold, Taylor, author; Kane, Michael (Michael John), author; Lewis, Bryan W. (Bryan Wayne), author (Boca Raton, FL : Taylor & Francis, CRC Press, 2019)
A Computational Approach to Statistical Learning gives a novel introduction to predictive modeling by focusing on the algorithmic and numeric motivations behind popular statistical methods. The text contains annotated code to over 80 original reference functions. These functions provide minimal working implementations of common statistical learning algorithms. Every chapter concludes with a fully worked out application that illustrates predictive modeling tasks using a real-world dataset. The text begins with a detailed analysis of linear models and ordinary least squares